Feasibility of quantifying SDC2 methylation in stool DNA for early detection of colorectal cancer - Oh, Tae Jeong; Oh, Hyun Il; Seo, Yang Yei; Jeong, Dongjun; Kim, Changjin; Kang, Hyoun Woo; Han, Yoon Dae; Chung, Hyun Cheol; Kim, Nam Kyu; An, Sungwhan (Clinical epigenetics, 2017)
Background Colorectal cancer (CRC) screening is the most efficient strategy to reduce disease-related mortality. Frequent aberrant DNA methylation is known to occur in selected genes and early during CRC development, which has emerged as a new epigenetic biomarker for early detection of CRC. Previously, we reported that we identified that CpG sites of SDC2 were aberrantly methylated in tumor tissues of most CRC patients through comprehensive methylation analysis and demonstrated a high potential of quantification of SDC2 methylation in blood for early detection of colorectal cancer. In this study, we aim to investigate the feasibility of quantifying SDC2 methylation in stool DNA for the early detection of CRC. The objective of this study was to confirm a high frequency of SDC2 methylation in tumor tissues at various stages of CRC and investigate the feasibility of a quantitative test for SDC2 methylation in fecal DNA by highly sensitive and accurate real-time PCR for early detection of CRC. Methods Bisulfite-pyrosequencing assay was performed to measure the SDC2 methylation status in tissue samples. For methylation analysis in stool DNA, a highly sensitive and accurate method was applied which implements consecutive two rounds of PCR consisting of unidirectional linear target enrichment (LTE) of SDC2 and quantitative methylation-specific real time PCR (qMSP) for SDC2 , named as me SDC2 LTE-qMSP assay. Its limit of detection was 0.1% methylation (corresponding to ~ 6 copies in total ~ 6200 genome copies). Results Positive SDC2 methylation was observed in 100% of primary tumors, 90.6% of adenomatous polyps, 94.1% of hyperplastic polyps, and 0% of normal tissues. SDC2 methylation level also significantly ( P < 0.01) increased according to the severity of lesions. In stool DNA test for SDC2 methylation by LTE-qMSP comparing CRC patients with various stages (I to IV) ( n = 50) and precancerous lesions ( n = 21) with healthy subjects ( n = 22), the overall sensitivity was 90.0% for detecting CRC and 33.3% for detecting small polyps, with a specificity of 90.9%. Conclusions Taken together, our result indicates that stool DNA-based SDC2 methylation test by LTE-qMSP is a potential noninvasive diagnostic tool for early detection of CRC.